Fossilized high pressure from the Earth's deep interior: The coesite-in-diamond barometer - Sobolev, Nikolai V. (The National Academy of Sciences, 2000)
Mineral inclusions in diamonds provide an important source of information about the composition of the continental lithosphere at depths exceeding 120–150 km, i.e., within the diamond stability field. Fossilized high pressures in coesite inclusions from a Venezuela diamond have been identified and measured by using laser Raman and synchrotron x-ray microanalytical techniques. Micro-Raman measurements on an intact inclusion of remnant vibrational band shifts give a high confining pressure of 3.62 (±0.18) GPa. Synchrotron single-crystal diffraction measurements of the volume compression are in accord with the Raman results and also revealed direct structural information on the state of the inclusion. In contrast to olivine and garnet inclusions, the thermoelasticity of coesite favors accurate identification of pressure preservation. Owing to the unique combination of physical properties of coesite and diamond, this “coesite-in-diamond” geobarometer is virtually independent of temperature, allowing an estimation of the initial pressure of Venezuela diamond formation of 5.5 (±0.5) GPa.